STUDY OF GREEN SPACE DEMAND TO REDUCE AIR POLLUTION LEVEL BY MOTORIZED VEHICLES EMISSION IN TANGERANG MUNICIPALITY - SHINTA DEWI (NIM 25407071); Pembimbing: Ir. IWAN KUSTIWAN, MT., MESI
Urban air quality was very influenced by motorized vehicles emission. Air pollution level has positive relation with the raise number of motorized vehicles in urban area. Significant roles and contributions of motorized vehicles in urban area to air quality make the availability of green space as an obligation in urban area planning and management.Green space supply became implementative solution to solve air pollution problems. The importance of green space in urban area persuaded government to obligate providing green space for about 30% from the area which is stated on Law No.26/2007 considering Spatial Planning. Consider the high volume of motorized vehicles mobility in Tangerang Municipality, it is important to study green space demand to reduce level of air pollution caused by motorized vehicles emission. The study will try to discover whether the obligation to provide green space 30% from area would solve the problem of air pollution from motorized vehicles emission. Study would include the determination of dominant factors for air quality level in Tangerang Municipality: green space area, land use or the scenario of local road network development. The study would only analyze emission gases which influenced number of ISPU (Air Pollution Standard Index): carbonmonoxide (CO), sulfur dioxide (SO2), particulat matter (PM10) and nitrogen dioxide (NOx). Precentage of green space to the area, analysis period, and the scenario of local road network development are the analyzed variables. The study would analyze spatially and has five stages. First to forecast number of every type of motorized vehicles as source of emission based on data about travel demand in Tangerang Municipality. Second, to calculate emission load using bottom-up method and also calculate pollutant gases concentration in the atmosphere. The third stage includes calculation of air quality which is stated in ISPU by converting pollution gases concentration to actual ISPU. Fourth stage is calculating green space demand to absorb pollutant gases in order to achieve health air quality standard. The last stage is to evaluate dominant factor influenced level of air quality in Tangerang Municipality by calculating frequency ISPU improvement on every variation percentage of green space area or scenario of local road network development. This last stage also includes evaluation of correlation between land use and air quality by overlaying spatial land use and spatial air quality. The study shown the obligation to provide green space 30% of the area would not always get to the achievement of health air quality standard. The high volume of travel demand caused air pollution and makes the high demand of green space, even more than 50% of the area for several zones. It means that green space could not be the only one solution in Tangerang Municipality to achieve health air quality standard. The air quality in Tangerang Municipality affected more by the scenario of local road network development rather than by expansion the green space area. Correlation between spatial land use and air quality shown that mixed land use would give minimum impact to air quality. The conclusion of this study is that even green space has reducing gases pollutant function, but the health air quality standard can be achived only by integrating action to reduce number of motorized vehicles as emission source. Based on this study, Local Government of Tangerang Municipality should consider air pollution aspect in spatial planning, local road network development and transportation system development since they all have significant roles and contributions to the air quality in Tangerang Municipality.